2600 phrases for effective performance reviews : ready-to-use words and phrases that really get results - Falcone, Paul (AMACOM, American Management Association, 2005)
For managers and professionals who know what they mean-- here's what to say.
Includes index.
Keywords: Employees -- Rating of -- Handbooks, manuals, etc.; Performance standards -- Handbooks, manuals, etc.; elektronické knihy; electronic books